Challenges and strategies for classroom management: Views of Primary Education Teachers - Καρούσιου, Χριστιάνα; Κατσικάς, Απόστολος (Education Sciences, 2025)
Classroom management is a critical parameter in shaping a learning environment that enhances the educational process and promotes the development of students. This study examines the views of 14 primary school teachers on the challenges they face in classroom management and the strategies they use to address them. Findings from the thematic analysis of semi-structured interviews highlight the main challenges, such as behaviour management, fostering team spirit, and adapting to the needs of students. To deal with them, teachers use strategies such as individualized instruction, reward systems, interactive activities and reinforcement of social-emotional skills, with an emphasis on collaboration with parents. The findings of the study enrich the debate on classroom management, providing further evidence for optimizing educational practice in Greek primary schools suggesting specific practices that can enhance teachers' work.